Feasibility study for the development of a Nigerian tuna fishery - Wise, J.P.; Ajayi, T.O. (Lagos, Nigeria Nigerian Institute for Oceanography and Marine Research, 1981)
A study of published and unpublished data and information leads to the conclusion that there is reasonable possibility of developing a profitable Nigerian tuna fishery for skipjack
osc 25/08/2021
Arch
Keywords: Fishery; Nigeria